If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-1)-2(3+5)=-3x+1
We move all terms to the left:
4(x-1)-2(3+5)-(-3x+1)=0
We add all the numbers together, and all the variables
4(x-1)-(-3x+1)-28=0
We multiply parentheses
4x-(-3x+1)-4-28=0
We get rid of parentheses
4x+3x-1-4-28=0
We add all the numbers together, and all the variables
7x-33=0
We move all terms containing x to the left, all other terms to the right
7x=33
x=33/7
x=4+5/7
| -(5x-3)=2-10(x+2) | | 5n2-32n-35=0 | | x=3+31/240 | | -5(2x-7)24=89 | | x+x+3=-5(x+x+1)-114 | | 2/3a-6=1/3a-9 | | 15.7·3.09+15.7·2.91=xx= | | 5x+62=3x+84 | | .25+6x(4-2x)=-95.75 | | 5x=24.50 | | -4(2x+4)=-16x+5 | | 500-2x=220 | | 5+17x=1495 | | y/2=(2y-18) | | 15=5x~13 | | 3/x=20/100 | | (8x^2-12)=(7x^2-4x) | | .25+16x(6-2x)=-127.75 | | 38=5+6a | | 8x+-16=-16x+5 | | 8x-7+2x=13 | | 146=9x+11 | | x/8-2=3/16 | | 6~8x=36 | | X=6+2/3y | | 2-9m+5+4m=2+8(5) | | 4.5+8x(7-2x)=-27.5 | | y/4+5=-4 | | -8x+11+9x=7+x+14 | | 3s-6-s=s=9 | | 3.95+0.08x=8.95+0.06x | | 3.95+0.08x=8.95+0.06 |